2013
DOI: 10.1111/1468-0327.12009
|View full text |Cite
|
Sign up to set email alerts
|

Bank ratings: what determines their quality?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
2
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 46 publications
(38 reference statements)
1
58
2
4
Order By: Relevance
“…18 Hypothesis 2. The informativeness of credit rating changes is high in a crisis period, and is 16 A similar argument is provided as well by Hau, Langfield, and Marques-Ibanez (2013) with respect to big banks. 17 This is also consistent with the model of Skreta and Veldkamp (2009), who motivate rating inflation via rating shopping.…”
Section: Hypotheses Developmentmentioning
confidence: 64%
“…18 Hypothesis 2. The informativeness of credit rating changes is high in a crisis period, and is 16 A similar argument is provided as well by Hau, Langfield, and Marques-Ibanez (2013) with respect to big banks. 17 This is also consistent with the model of Skreta and Veldkamp (2009), who motivate rating inflation via rating shopping.…”
Section: Hypotheses Developmentmentioning
confidence: 64%
“…It is always difficult to decide how much any upturn reflects enduring changes and how much simply a cyclical improvement that will disappear in due course. Natural optimism might suggest an upward bias but Hau et al (2012) suggest that rating agencies have a relative bias as well. The same conflicts of interest that may contribute to this bias do not apply to the authorities.…”
Section: Early Warning Systemsmentioning
confidence: 99%
“…l a r c i e r may be important. Hau, Langfield, and Marqués-Ibañez (2012) suggest that rating agencies systematically underestimate the relative risks of larger banks, in part because they feel they are too-big-to-fail, but also because those banks can exert disproportionate influence on the raters. While we use what are apparently Standardized beta coefficients; t statistics in parentheses * p < 0.05, ** p < 0.01, *** p < 0.001 l a r c i e r unbiased measures of the state of the bank, it is possible that the authorities may not react unambiguously to the sign of fragility irrespective of size of the bank.…”
Section: Test Of Robustnessmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, Hau, Langfield and Marques-Ibanez (2013), by examining the quality of the BCRR attributed by the three largest CRAs in 16 countries (United States of America and 15 countries of Europe) between 1990-2011, found that on average, the big banks receive higher ratings which help to perpetuate the existence of the principle of "TBTF" of banks.…”
Section: Size Of the Bankmentioning
confidence: 99%